Development of telephone supportive self care model and evaluation of its impacts on glycemic control and self care among type II diabetic patients in Bangkok metropolitan - Nittayawan Kulnawan (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2010